Elucidation of the protein composition of mouse seminal vesicle fluid. Issue 9 (19th January 2022) - Smyth, Shannon P.; Nixon, Brett; Anderson, Amanda L.; Murray, Heather C.; Martin, Jacinta H.; MacDougall, Lily A.; Robertson, Sarah A.; Skerrett‐Byrne, David A.; Schjenken, John E.
Abstract: The seminal vesicles are male accessory sex glands that contribute the major portion of the seminal plasma in which mammalian spermatozoa are bathed during ejaculation. In addition to conveying sperm through the ejaculatory duct, seminal vesicle secretions support sperm survival after ejaculation, and influence the female reproductive tract to promote receptivity to pregnancy. Analysis of seminal vesicle fluid (SVF) composition by proteomics has proven challenging, due to its highly biased protein signature with a small subset of dominant proteins and the difficulty of solubilizing this viscous fluid. As such, publicly available proteomic datasets identify only 85 SVF proteins in total. To address this limitation, we report a new preparative methodology involving sequential solubilization of mouse SVF in guanidine hydrochloride, acetone precipitation, and analysis by label‐free mass spectrometry. Using this strategy, we identified 126 SVF proteins, including 83 previously undetected in SVF. Members of the seminal vesicle secretory protein family were the most abundant, accounting for 79% of all peptide spectrum matches. Functional analysis identified inflammation and formation of the vaginal plug as the two most prominent biological processes. Other notable processes included modulation of sperm function and regulation of the female reproductive tract immune environment. Together, these findings provide a robust methodological framework for future SVF studies and identify novel proteins with potential to influence both male and female reproductive physiology.